TRAUMATIC BRAIN INJURY: IMPACT ON VETERANS - Muller, Elva (Acta Scientiae et Intellectus, 2024)
Traumatic brain injury (TBI) is a frequent but under diagnosed condition that is associated with a number of comorbidities. It affects countless numbers of servicemen and women who were in combat in Iraq (Operation Iraqi Freedom) and Afghanistan (Operation Enduring Freedom). TBI is a disturbance of normal brain function that occurs when the head is suddenly thrust out of position. It can be a closed or open injury. It affects the ability to think effectively. TBI co-occurs with chronic pain, PTSD, and suicide. It is unique to the individual and can present with an array of different symptoms. The pain usually manifests as a headache, nociceptive pain, or neuropathic pain. This pain usually ranges from moderate to severe. Post traumatic disorder is the result of exposure to a severe stressor that threatens one’s life or physical integrity. OEF/OIF service members were exposed to high rates of trauma therefore developing Posttraumatic disorder. PTSD and depression are major mental health concerns for the patient diagnosed with traumatic brain injury. Traumatic brain injury in conjunction with chronic pain, PTSD and depression can be devastating. Veterans have a higher rate of suicide than the general population, therefore those with those with dual diagnoses are at highest risk. Clinical awareness is crucial in promoting overall well-being for these patients.